Changing the Reactivity of Zero‐ and Mono‐Valent Germanium with a Redox Non‐Innocent Bis(silylenyl)carborane Ligand. (1st June 2021) - Yao, Shenglai; Kostenko, Arseni; Xiong, Yun; Lorent, Christian; Ruzicka, Ales; Driess, Matthias
Abstract: Using the chelating C, C′‐bis(silylenyl)‐ortho‐dicarborane ligand, 1, 2‐(RSi)2 ‐1, 2‐C2 B10 H10 [R=PhC(NtBu)2 ], leads to the monoatomic zero‐valent Ge complex ("germylone") 3 . The redox non‐innocent character of the carborane scaffold has a drastic influence on the reactivity of 3 towards reductants and oxidants. Reduction of 3 with one molar equivalent of potassium naphthalenide (KC10 H8 ) causes facile oxidation of Ge 0 to Ge I along with a two‐electron reduction of the C2 B10 cluster core and subsequent Ge I ‐Ge I coupling to form the dianionic bis(silylene)‐supported Ge2 complex 4 . In contrast, oxidation of 3 with one molar equivalent of [Cp2 Fe][BC6 H3 (CF3 )2 4 ] as a one‐electron oxidant furnishes the dicationic bis(silylene)‐supported Ge2 complex 5 . The Ge 0 atom in 3 acts as donor towards GeCl2 to form the trinuclear mixed‐valent Ge 0 →Ge II ←Ge 0 complex 6, from which dechlorination with KC10 H8 affords the neutral Ge2 complex 7 as a diradical species. Abstract : The bis(silylenyl) ortho ‐dicarborane‐supported zero‐valent Ge complex (germylone) 1 undergoes facile dimerization with Ge−Ge bond formation upon one‐electron oxidation and reduction to furnish the bis(silylene)‐supported dicationic and dianionic [Ge I –Ge I ] complexes 2 and 3, respectively. A neutral complex 4 bearing a Ge2 2+ dumbbell embedded in a shell of two radical‐anionic di(silylenyl)dicarborane ligands could be synthesized.